Frutos, semillas y plántulas de Costa Rica - Vargas Rojas, Gustavo (Editorial Universidad Nacional (EUNA), 2018)
This work is comprised of 4 volumes that seek to help the reader identify by name the innumerable species of plants that inhabit the Costa Rican territory. People know plants by their stems and leaves, but they are mostly unaware of the type of fruit, the shape of the seeds, as well as the plant at sprouting. The information offered by Fruits, seeds and seedlings of Costa Rica, can be used as reference material because it is very useful to understand and complement the studies of dispersal and plant demography.